Stiff-Person Syndrome: Case Series - Yu Jin Jung; Han G. Jeong; Ryul Kim; Han-Joon Kim; Beom S. Jeon (Journal of Movement Disorders, 2014)
Stiff-person syndrome (SPS) is a rare disorder, characterized by progressive fluctuating muscular rigidity and spasms. Glutamic acid decarboxylase (GAD) antibody is primarily involved in the pathogenesis of SPS and SPS is strongly associated with other autoimmune disease. Here we report three cases of patients with classical SPS finally confirmed by high serum level of GAD antibodies. All of our patients respond favorably to gamma amino butyric acid-enhancing drugs and immunotherapies.